2023
DOI: 10.48550/arxiv.2302.14296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrete-time Optimal Covariance Steering via Semidefinite Programming

Abstract: This paper addresses the optimal covariance steering problem for stochastic discrete-time linear systems subject to probabilistic state and control constraints. A method is presented for efficiently attaining the exact solution of the problem based on a lossless convex relaxation of the original non-linear program using semidefinite programming. Both the constrained and the unconstrained versions of the problem with either equality or inequality terminal covariance boundary conditions are addressed. We first p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We mentioned three other policy parametrizations that are used to solve covariance steering problems in the literature, namely the state feedback, 20 state history feedback, 31 and auxiliary variable feedback 44 policies. It is shown that the optimal policy parametrization for the covariance steering problem is the state feedback policy parametrization, 20,45 and optimal policy parameters for an instance of the covariance steering problem can be efficiently found by the associated SDP. However, the presence of chance-constraints, defined as in (13), violates the convexity of the optimization-based formulation of the covariance steering problem as a SDP.…”
Section: Control Policy Comparison With Existing Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…We mentioned three other policy parametrizations that are used to solve covariance steering problems in the literature, namely the state feedback, 20 state history feedback, 31 and auxiliary variable feedback 44 policies. It is shown that the optimal policy parametrization for the covariance steering problem is the state feedback policy parametrization, 20,45 and optimal policy parameters for an instance of the covariance steering problem can be efficiently found by the associated SDP. However, the presence of chance-constraints, defined as in (13), violates the convexity of the optimization-based formulation of the covariance steering problem as a SDP.…”
Section: Control Policy Comparison With Existing Approachesmentioning
confidence: 99%
“…This policy parametrization is optimal for unconstrained covariance steering problems in both continuous-time 7 and discrete-time. 20,45,46 While Reference 20 suggests a randomized version of the latter policy, it is proven that at optimality, the randomized component is zero, making the optimal policy a deterministic state feedback policy. 20 Under the state feedback policy parametrization, the dynamics of the state mean and the state covariance are given as follows:…”
Section: State Feedback Policymentioning
confidence: 99%
See 1 more Smart Citation
“…In the sequel, and similar to [38], we treat the moments of the intermediate states {Σ k , µ k } N −1 k=1 in the steering horizon as decision variables in the resulting optimization problem.…”
Section: Problem Reformulationmentioning
confidence: 99%
“…As safety requirements in robotics and control are of great significance, covariance steering (CS) theory has recently emerged as a promising approach for guiding the state distribution of a system to prescribed targets while providing probabilistic safety guarantees [3,4,10,20]. Successful robotics applications can be found in trajectory optimization [5,34], path planning [23], flight control [7,17,27], multi-robot systems [31,33] and robotic manipulation [18], to name a few. While the main barrier for applying CS methods for multi-agent stochastic control was due to their significant computational requirements, recent distributed optimization based approaches [31,33] have shown that CS is a viable option for multi-agent systems.…”
Section: Introductionmentioning
confidence: 99%